Application of Scheduled Drawing Therapy to Reduce Signs and Symptoms of Auditory Hallucinations - Silvia Firsa Permata; Wita Oktaviana; Joko Purnomo (Sarana Ilmu Indonesia (salnesia), 2026)
Auditory hallucinations are a common problem in individuals with severe mental disorders that affect cognitive, emotional, and behavioral functioning and reduce quality of life. This study aimed to determine the effect of scheduled drawing therapy on reducing the signs and symptoms of auditory hallucinations. The method used was a case study with a nursing care approach involving three patients. The intervention was conducted for five consecutive days using structured drawing activities. The results showed a decrease in signs and symptoms in all patients, indicated by reduced self-talking behavior, fear, and improved focus and self-control. It is concluded that scheduled drawing therapy is effective in reducing auditory hallucination symptoms and is recommended as a supportive intervention in mental health nursing practice.